A contribution to the taxonomic knowledge of the genus \(Thrinchostoma (Thrinchostoma\) s. str.) Saussure (Hymenoptera: Halictidae) from Vietnam, with new records of three species and a key to species - Thi Ngat, Tran; Thi Hoa, Dang; Phuong Lien, Nguyen Thi; Thi Giang, Phan; Thanh Truc, Truong (Academia Journal of Biology, 2023)
Four species of the little-known bee genus Thrinchostoma Saussure, 1890 from Vietnam are presented including Thrinchostoma (Thinchostoma s. str.) tonkinense Blüthgen, 1926 and three new records: T. (T.) flaviscapus Bülthgen, 1926; T. (T.) sladeni Cockerell, 1913; and T. (T.) yunnanense Niu & Zhu, 2016. The occurrence of T. (T.) tonkinense Blüthgen, 1926 in Vietnam is confirmed. A key to species and distribution map of four species of the genus Thrinchostoma are also provided for Vietnam.